Characterizing the Lower Paleolithic bone industry from Schöningen 12 II: A multi-proxy study. Issue 89 (December 2015) - Julien, Marie-Anne; Hardy, Bruce; Stahlschmidt, Mareike C.; Urban, Brigitte; Serangeli, Jordi; Conard, Nicholas J.
Abstract: Although preservation of Paleolithic faunal assemblages from open-air settings is often poor, the Lower Paleolithic sites of Schöningen provide exceptionally well-preserved mammalian faunal material for investigating hominin/animal relationships. Pleistocene fossil assemblages, however, usually reflect a complex taphonomic history in which natural and anthropogenic processes are often superimposed. A number of examples of osseous finds that resemble tools were recently discovered in the MIS 9 deposits of Schöningen 12 II. Non-anthropogenic agents are known to produce surface modifications mimicking human artifacts and the identification of osseous remains used and/or deliberately modified by ancient hominins is often controversial in such old contexts. Multiple lines of evidence are thus useful for distinguishing between osseous artifacts and "eco-facts". In this paper, the recognition of the use of bone for different technological purposes by late Middle Pleistocene hominins is addressed through a multi-proxy study combining geoarcheology, bone taphonomy, zooarcheology, and use-wear analysis. This allowed the identification of the processes and agents responsible for the formation and modification of the different bone assemblages of Schöningen 12 II. Our analysis points to different types of bones having been likely used as tools. These results expand the diversity of the organic technological repertoire of the Middle Pleistocene hominins, making Schöningen 12 II a remarkable new source of information on osseous technology long before the Upper Paleolithic, the period traditionally viewed as the start of the systematic use of bone tools. Together with other observations of bone tools documented during the Lower and Middle Paleolithic, the results from Schöningen show that archeologists may have underestimated the diversity and importance of osseous technology among archaic hominins.